Mixed Integer Linear Programming Applied to Adaptive Directional Overcurrent Protection Considering N-1 Contingency - Martin, Klaus Tesser; Marchesan, Adriano Cavalheiro; de Araujo, Olinto Cesar Bassi; Cardoso, Ghendy; da Silva, Marcelo Freitas (IEEE transactions on industry applications, 2023)
This work proposes a methodology for directional overcurrent protection coordination in interconnected transmission systems considering a possible network contingency state. The methodology uses the short-circuit data of the current network topology; however, the maximum load current data in the protection section of each relay is obtained considering the n-1 criterion, already foreseeing the disconnection of some network line. Thus, if a line gets disconnected, other protective devices will not improperly actuate by the redistribution of load currents in the network. The objective is to propose an adaptive protection scheme to redo the coordination for each topological change in the network. To this end, this work considers a smart grid environment with a supervisory system with communication capability between this and the remote devices. To obtain the optimal performance, the coordination problem, originally non-linear and non-convex, is linearized, allowing its formulation as a Mixed Integer Linear Programming problem. The methodology is applied to the 8-bus test system in 3 different cases and the 30-bus test system. Results show that the optimal coordination is obtained in a fast computational processing time, showing the suitability of the methodology for real-time application.